Quantification of relation between disease intensities and physiological and biochemical changes in mulberry due to greyleaf spot - Pratheesh Kumar, P.; Qadri, S.; Pal, Sebely; Misra, A. (2011)
In order to understand virtual loss due to pathogenesis, quantitative determination of biochemical constitutions and physiological alterations were made at various intensities (1-5%, 6-15%, 16-30%, 31-50% and >50% leaf area infected) of grey leaf spot (Pseudocercospora mori) in mulberry in comparison with healthy leaves. Biochemical constituents such as total chlorophyll, total soluble sugar and total protein declined while, total phenol content increased significantly due to pathogen infection. Chlorophyll (r 2=0.92), sugar (r 2=0.85) and protein (r 2=0.83) contents showed negative whereas, phenol (r 2=0.61) showed positive correlation with intensity of the disease. Similarly, photosynthetic rate, transpiration rate stomatal conductance, leaf moisture content and instantaneous water use efficiency (WUEi) decreased significantly (P<0.05), whereas, stomatal resistance increased in the infected leaves. Physiological parameters also showed significant correlation with disease intensity. Photosynthetic rate (r 2=0.95), transpiration rate (r 2=0.84), stomatal conductance (r 2=0.57), physiological water use efficiency (r 2=0.83), and leaf moisture content (r 2=0.95) were negatively correlated and stomatal resistance (r 2=0.92) was positively correlated with the disease intensity.